2020
DOI: 10.3847/1538-4357/ab7fa2
|View full text |Cite
|
Sign up to set email alerts
|

Radial Evolution of Magnetic Field Fluctuations in an Interplanetary Coronal Mass Ejection Sheath

Abstract: The sheaths of compressed solar wind that precede interplanetary coronal mass ejections (ICMEs) commonly display large-amplitude magnetic field fluctuations. As ICMEs propagate radially from the Sun, the properties of these fluctuations may evolve significantly. We have analyzed magnetic field fluctuations in an ICME sheath observed by MESSENGER at 0.47 au and subsequently by STEREO-B at 1.08 au while the spacecraft were close to radial alignment. Radial changes in fluctuation amplitude, compressibility, inert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
47
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 30 publications
(64 citation statements)
references
References 44 publications
(64 reference statements)
14
47
3
Order By: Relevance
“…This is in contrast with the sheath analysed by Good et al (2020), who found clear differences between the solar wind ahead and in the sheath at the orbit of Mercury, but not near the orbit of Earth. However, they investigated fluctuations throughout the sheath collectively, while we have investigated three sub-regions separately.…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…This is in contrast with the sheath analysed by Good et al (2020), who found clear differences between the solar wind ahead and in the sheath at the orbit of Mercury, but not near the orbit of Earth. However, they investigated fluctuations throughout the sheath collectively, while we have investigated three sub-regions separately.…”
Section: Discussioncontrasting
confidence: 98%
“…. In all instances, it can be seen that compressibility generally decreases from the smallest scales until about 100 s. This is a well known trend from previous solar wind studies (e.g., Chen et al, 2015;Matteini et al, 2018;Good et al, 2020). We note that the increase for the few highest timescales could be related to statistical errors in the data as discussed above.…”
Section: Compressibilitysupporting
confidence: 80%
See 3 more Smart Citations